Effects of Communicable Diseases on Maternity Services in Selected MNCH Priority Counties’ Public Health facilities in Kenya: A Case of COVID-19 - Matiang’i , M.; Okoro, D.; Ngunju, P.; Oyieke, J. (International Journal of Current Aspects, 2023)
Covid-19 is a rapidly evolving pandemic which has affected both developed and developing countries. Maternity services in low resource countries are adapting to provide antenatal and postnatal care midst a rapidly shifting health system environment due to the COVID-19 pandemic. Over the years there has been progress in reducing maternal and new-born mortality and stillbirths in Kenya and the globe. However, in the wake of covid-19 pandemic, perinatal women and their frontline health services providers especially nurses and midwives have been cited to bear the brunt of the pandemic. This has largely been linked to the limited access to Personal Protective Equipment (PPE) requirements and the fear of contracting the disease within health services delivery points. There have been adverse effects of maternal and new-born care outcomes due to coronavirus disease. The objective of this study was to determine the effect of coronavirus disease (COVID 19) to maternity services in selected levels III and IV public health facilities within five (5) Counties in Kenya. The five MNCH priority counties selected included Nairobi, Migori, Kilifi, Isiolo and Garissa. A two-stage sampling approach was used to select health facilities in the 5 MNCH priority counties with the sampling frame comprising all MNCH priority counties in Kenya. The study employed cross-sectional and observational retrospective approaches. Data was collected from the midwifery managers and maternity registers in a total of 28 levels III and IV facilities. Open Data Kit (ODK) formatted tools were used to collect data from maternity services facility managers and maternity registers in the selected facilities. Data collected from maternity registers covered the period of four months before covid-19 pandemic and four months during the covid-19 pandemic. A two-days training programme comprising of introduction to study objectives and instruments as well as review of the instruments, practice interviews and data collection was conducted. Data was analysed using STATA Version 15. Descriptive statistics and measures of central tendencies were used to analyse the demographic details of the respondents and health related variables of interests. Chi-square test and fishers exact test were used to find association between facilities that had diagnosed COVID-19 cases and their demographic characteristics. For all tests, a p-value < 0.05 was taken as statistically significant. A total of 31 midwifery managers were interviewed and a total of 801 maternity records (400 before COVID and 401 during COVID-19 pandemic) were obtained from levels 3 III (66%) and IV (34%) facilities across 5 MNCH priority counties in Kenya [Nairobi (27%), Garissa (10%), Isiolo (20%), Kilifi (23%) and Migori (20%)]. On Overall representation, Level III facilities were slightly over half (51.6%) and level IV facilities had 48.4% representation. Most of the maternity services managers interviewed (48.4%) had worked for less than 3 years in their respective stations and the majority (67.7%) had a diploma in either Nursing or midwifery as their highest level of professional education. Overall, the managers indicated that ANC visits had reduced (67.9%), referrals of mothers with complications got delayed (29%), mothers feared delivering in hospitals (64.5%) and possibly some mothers were delivering with the assistance of TBAs (45.2%). The managers reported that New-born care services were the most affected by the pandemic (54.8%) followed by ANC services (45.2%). Immunization services were the least affected (35.5%). The managers (41.9%) reported reduced uptake of FP commodities and a reduction in exclusive breastfeeding (12.9%). Majority (51.6%) of the managers confirmed there was an increase of unplanned pregnancies (90.4) during the pandemic period with limited opportunity to educate ANC clients (74.2%). It was observed that 48% of the facilities surveyed had diagnosed a covid-19 case yet only 61.3% and 54.8% of the facilities had access to masks and hand sanitizers respectively. Facility records indicated a 19% higher ANC attendance before COVID than during COVID-19 pandemic period. Neonatal deaths increased significantly during Covid-19 period ((P=0.010) by 38%. Live births significantly increased by 15% during the pandemic (p<0.0001). Other significant increases were observed in mothers with labour complications (p=0.0003) and number of mothers that underwent caesarean sections(p<0.001) during the pandemic period. There was no sufficient statistical evidence on whether the uptake of FP commodities, post-partum complications, immunizations and maternal mortalities were affected by the covid-19 pandemic. The Covid-19 pandemic caught maternity service providers and the local health systems unaware. The fear of the pandemic had a cross-cutting effect on utilisation of maternity services. Continuous training of health services providers on emergency response to pandemics and health system preparedness is vital in order to have resilient service delivery points.
Keywords: Covid-19; maternity services; frontline health workers; Pandemic